Hodnocení kvality života pacientů s degenerativním onemocněním bederní páteře - Němec, Filip; Chaloupka, Richard; Krbec, Martin; Messner, Petr (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2009)
The review article deals with issues related to the evaluation of life quality, using questionnaire techniques, in patients with degenerative disorders of the lumbar spine. The topic is introduced with the complexity of health definition and life quality evaluation. Then degenerative spinal disorders are defined. The options for assessment of success in surgical treatment of degenerative spine by both objective and subjective methods are presented. The use of questionnaires and distinction between generic and specific ones are described, advantages and disadvantages are analysed and the most important types of questionnaires currently used in international studies, and recently also in this country, are mentioned. Complications associated with the use of these methods are shown. The paper is concluded with a brief summary of the data presented. The aim of this paper is to stimulate interest in attending surgeons so that they should pay attention to the evaluation of outcomes in their patients and thus provide relevant data for comparison with the international literature.
Keywords: kvalita života; nemoci páteře; Lumbar Vertebrae; průzkumy a dotazníky; Spinal Diseases; Humans; lidé; Quality of Life; bederní obratle; Surveys and Questionnaires